أثر أنماط ما وراء الانفعال الوالدي في تطور نظرية العقل لدى أطفال ما قبل المدرسة - الربابعة، حمزة عبدالكريم; الخطيب، مروة عماد (جامعة اليرموك - عمادة البحث العلمي, 2022)
هدفت الدراسة إلى الكشف عن أثر أنماط ما وراء الانفعال الوالدي في تطور نظرية العقل، لدى عينة تكونت من (174) طفلا من مرحلة ما قبل المدرسة، وأولياء أمورهم، تم اختيارهم بالطريقة المتيسرة من محافظة إربد، خلال الفصل الأول من العام الدراسي 2020/2021. وأظهرت النتائج وجود مستوى مرتفع لنمط ما وراء الانفعال الوالدي (رفض الانفعالات السلبية)، ومستوى متوسط لأنماط (تقبل الانفعالات السلبية، والتدريب على الانفعالات، ومشاعر عدم اليقين). وبينت النتائج وجود فروق في نمط (التدريب على الانفعالات) لدى الآباء، تعزى لمتغير الترتيب الولادي، لصالح الطفل الأول، ووجود فروق في نمط (مشاعر عدم اليقين) لدى الأمهات تعزى لمتغيري الجنس لصالح الإناث، والترتيب الولادي لصالح الطفل الأول، وأشارت النتائج إلى وجود مستوى متوسط من تطور نظرية العقل، وعدم وجود فروق في تطور نظرية العقل تعزى لمتغيرات جنس الطفل، وترتيبه الولادي، والمستوى التعليمي للوالدين. كذلك كشفت النتائج وجود أثر لأنماط ما وراء الانفعال الوالدي (التدريب على الانفعالات، ورفض الانفعالات السلبية، ومشاعر عدم اليقين) في نظرية العقل، حيث فسرت ما نسبته (45.6%) من التبـاين في مستوى الأداء على مهمات نظرية العقل لدى أطفال ما قبل المدرسة. This study aimed to reveal the effect of parental meta – emotion patterns on the theory of mind in a sample that consisted of (174) pre – school children and their parents, who were Chosen using the available method, from Irbid governorate during the first semester of the academic year 2020/2021. The results showed that there is a high level of the parental meta–emotion pattern (rejection of negative emotions) and a medium level of the patterns acceptance of negative emotion, emotion coaching and feelings of uncertainty). The results also showed that there are differences in the pattern of (emotion coatching) among fathers due to the variable of birth arrangement in favor of the first child and in the pattern (feelings of uncertainty) among mothers due to the variable of gender in favor of girls and due to the variable of birth arrangement in favor of the first child. The results also indicated that there is a medium level of development of the theory of mind, as well as the absence of differences in the development of the theory of mind due to the variables of the child's gender, birth order and the educational level of the parents. The results also revealed that there is an effect of parental meta emotion (emotion cotching, rejection of negative emotions and feelings of uncertainty) on the theory of mind, where those patterns explained (%45.6) of the variance in the level of performance on the tasks of the theory of mind among pre-schoolers'.
Keywords: السلوكيات الانفعالية -- نظرية العقل -- الأمن الانفعالي -- الرعاية الأسرية -- أطفال الروضة